THE INFLUENCE OF FOOTBALL SPORTS CLUBS IN HIGH SCHOOLS ON THE DEVELOPMENT OF PHYSICAL QUALITIES OF 12-13-YEAR-OLD STUDENTS (Academicia Globe: Inderscience Research, 2022)
This is in the article students for general education in their schools organize to be done from class except affairs and his structural part has been football sports circles importance and 12-13 years old student children physical qualities i.e agility , quickness, strength, endurance, flexibility effect about theoretical info and practical recommendations statement done